Limited detection of small (≤ 10 mm) colorectal liver metastasis at preoperative CT in patients undergoing liver resection. - Yousun Ko; Jihang Kim; Joseph Kyu-Hyung Park; Haeryoung Kim; Jai Young Cho; Sung-Bum Kang; Soyeon Ahn; Kyong Joon Lee; Kyoung Ho Lee (PLoS ONE, 2017)
To retrospectively determine the sensitivity of preoperative CT in the detection of small (≤ 10 mm) colorectal liver metastasis (CRLM) nodules in patients undergoing liver resection.The institutional review board approved the study and waived informed consent. We included 461 pathologically confirmed CRLM nodules in 211 patients (including 71 women; mean age, 66.4 years) who underwent 229 liver resections following abdominal CT. Prior to 163 resections, gadoxetic acid-enhanced liver MR imaging was also performed. Nodules were matched between pathology reports and prospective CT reports following a predefined algorithm. Per-nodule sensitivity of CT was calculated by nodule-size category. Generalized estimating equations were used to adjust for within-case correlation.Fourteen nodule sizes were missing in the pathology report. Nodules of 1-5 mm and 6-10 mm accounted for 8.1% (n = 36) and 23.5% (n = 105) of the remaining 447 nodules, and the number of nodules gradually decreased as nodule size increased beyond 10 mm. The overall sensitivity of CT was 81.2% (95% confidence interval, 77.1%, 85.2%; 365/461). The sensitivity was 8% (0%, 17%; 3/36), 55% (45%, 65%; 59/105), 91%, 95%, and 100% for nodules of 1-5 mm, 6-10 mm, 11-15 mm, 16-20 mm, and >20 mm, respectively. The nodule-size distribution was similar between resections undergoing gadoxetic acid-enhanced MR imaging and those not undergoing the MR imaging.CT has limited sensitivity for nodules of ≤ 10 mm and particularly of ≤ 5 mm.